2012
DOI: 10.1083/jcb.201201024
|View full text |Cite
|
Sign up to set email alerts
|

Overlap of cargo binding sites on myosin V coordinates the inheritance of diverse cargoes

Abstract: Vacuole- and mitochondria-specific cargo adaptors compete for an overlapping binding site on Myo2 to determine the inheritance of these organelles during budding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
106
3
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(122 citation statements)
references
References 48 publications
9
106
3
4
Order By: Relevance
“…S8). Previous studies of yeast myo2p suggested the site 2 in yeast MyoV is involved in binding to several target proteins; many of these proteins do not have corresponding counterparts in mammals (7,8), indicating that both MyoV-GTD and its cargos undergo extensive changes during evolution. Despite of the high-sequence similarity between MyoVa and Vb, neither RILPL2 nor MLPH shows specific binding to MyoVb-GTD, indicating exquisite cargo-binding specificities of the closely related MyoV paralogs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S8). Previous studies of yeast myo2p suggested the site 2 in yeast MyoV is involved in binding to several target proteins; many of these proteins do not have corresponding counterparts in mammals (7,8), indicating that both MyoV-GTD and its cargos undergo extensive changes during evolution. Despite of the high-sequence similarity between MyoVa and Vb, neither RILPL2 nor MLPH shows specific binding to MyoVb-GTD, indicating exquisite cargo-binding specificities of the closely related MyoV paralogs.…”
Section: Discussionmentioning
confidence: 99%
“…Several cargo-binding sites have been identified in yeast myo2p via structure-based, mutagenesis-based experiments (7,8). Interestingly, the cargo-binding surface in subdomain I of myo2p, which is critical for binding to vacuole-or mitochondrialspecific cargos, partially overlaps with the corresponding MLPHbinding surface on MyoVa (Fig.…”
Section: Myova-gtd Uses Different Sites To Interact With Rilpl2 and Mmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now known that these myosins, (e.g., in classes, I, V, VI, VII, IX and X) contain cargo-binding domains in their tail regions, which bind select adaptor proteins that target these myosins to specialized compartments/organelles within the cell where they perform specific functions. In the case of myosin V and VI there is structural data available on the cargo binding interfaces involved [86][87][88], which could serve as templates to design specific inhibitors. Thus, by targeting unique myosin-adaptor protein interactions, one could manipulate a specific adaptor protein-related motor function linked to distinct step(s) along a pathway within specialized cells.…”
Section: Future Perspectivementioning
confidence: 99%
“…25,26 Two additional proteins, Ypt11 and Mmr1, interact with the cargo-binding domain on the Myo2 tail and participate in mitochondrial inheritance. 27,28 A recent study using live cell microscopy revealed that Num1 is required for attachment of mitochondria to the cell cortex and retention in mother cells, and that expression of chimeric plasma membrane tethers rescued mitochondrial fission defects in ∆num1 and ∆mdm36 mutants. 20 The pattern of mitochondrial distribution is closely linked to the cell cycle, and is demonstrated by time-lapse imaging of mitochondria in the cell cycle of budding yeast.…”
Section: Budding Yeastmentioning
confidence: 99%